The value, objectives and objects of analysis of production costs. (Journal of Economic Research & Business Administration, 2016)
Analysis of the cost of goods, works and services is critical. It allows to reveal tendencies of change of this indicator, the implementation of the plan, to determine the influence of factors, and its growth and on this basis to assess the operation of the enterprise to use opportunities and to establish reserves to reduce production costs. The cost of production is inseparably linked with almost all indicators of economic activity of the enterprise, and they get it reflected. From this point of view, this indicator summarizes the quality of the whole work of the enterprise. The article gives the definition of the cost of production and discusses the importance, objectives and objects of analysis of production costs. And due to the large volume of production and its continuous growth, as the decrease of one of the elements of costs cost can lead to increased competitiveness and profitability of products, indicated the importance of this analysis.
Keywords: analysis of production costs; value analysis; objectives of cost analysis; sources of information; the objects of analysis; costs.